2021
DOI: 10.7717/peerj.11616
|View full text |Cite
|
Sign up to set email alerts
|

Alpha- and beta- adrenergic receptors regulate inflammatory responses to acute and chronic sleep fragmentation in mice

Abstract: Sleep is a recuperative process, and its dysregulation has cognitive, metabolic, and immunological effects that are largely deleterious to human health. Epidemiological and empirical studies have suggested that sleep fragmentation (SF) as result of obstructive sleep apnea (OSA) and other sleep abnormalities leads to pronounced inflammatory responses, which are influenced by the sympathetic nervous system (SNS). However, the underlying molecular mechanisms contributing to SNS regulation of SF-induced inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
2
8
2
Order By: Relevance
“…The brain responses for IL-1β gene expression were similar compared to TNFα but earlier. These results are a departure from previous studies that have shown elevated pro-in ammatory gene expression in hypothalamus, hippocampus, and pre-frontal cortex after 24-h of sleep fragmentation among female C57BL/6J mice 17,18 , but very few effects observed among males 10,23 , although there was a non-signi cant trend for increased pro-in ammatory gene expression in hippocampus in one study 12 . Reasons for this discrepancy are unclear, but could involve differences in how hippocampus was extracted from the brain in these different studies (whole vs. partial dissection).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The brain responses for IL-1β gene expression were similar compared to TNFα but earlier. These results are a departure from previous studies that have shown elevated pro-in ammatory gene expression in hypothalamus, hippocampus, and pre-frontal cortex after 24-h of sleep fragmentation among female C57BL/6J mice 17,18 , but very few effects observed among males 10,23 , although there was a non-signi cant trend for increased pro-in ammatory gene expression in hippocampus in one study 12 . Reasons for this discrepancy are unclear, but could involve differences in how hippocampus was extracted from the brain in these different studies (whole vs. partial dissection).…”
Section: Discussioncontrasting
confidence: 99%
“…The ndings indicate that pro-in ammatory responses to acute sleep fragmentation are tissue-speci c, which is consistent with previous studies [16][17][18]23 . ASF increased TNFα expression in heart and EWAT after exposure for 12 and 24 h, respectively, but there was no effect in liver or spleen.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the specific role of SNS activation in the immune phenotype associated with sleep deprivation is not clearly established, data suggest a proinflammatory effect of SNS under sleep deprivation. Indeed, chemical sympathectomy has been recently shown to alleviate the inflammatory response following chronic sleep deprivation in mice 255 , and both αand, to a lesser extent, β-adrenergic receptors seem to contribute to the sympathetic regulation of inflammatory responses to sleep deprivation 256 .…”
Section: Immune Mechanisms Linking Sleep Deprivation and Diseasesmentioning
confidence: 99%
“…It has been proposed that alterations in these immunoregulatory hormones may contribute to this pro-inflammatory phenotype 14 . This hypothesis has received empirical support using chemical sympathectomy and pharmacological blockade of adrenergic receptors to demonstrate that SNS suppression ameliorates inflammation from experimental sleep fragmentation in mice 15 , 16 . An additional hypothesis to explain inflammation from sleep loss involves vascular changes associated with increased blood pressure as a result of increased sympathetic output from prolonged wakefulness 14 , 17 .…”
Section: Introductionmentioning
confidence: 99%